CRIMP: Here crisis mapping goes offline. (15th November 2019) - Paul, Partha Sarathi; Ghosh, Bishakh Chandra; Dutta, Hridoy Sankar; De, Kingshuk; Basu, Arka Prava; Pramanik, Prithviraj; Saha, Sujoy; Chakraborty, Sandip; Ganguly, Niloy; Nandi, Subrata
Abstract: Online Crisis Mapping Systems (CMS) are de facto tools to facilitate disaster response, although they may fail to work during the initial days of large-scale (Level 3) natural disasters, because of the unavailability of Internet due to the breakdown of existing communication infrastructures and the power-grids. In this paper, we present a novel end-to-end application system, called CRIMP, which can run both as an Android App in users' smartphones as well as an application in custom portable units, referred as Information Storage Boxes (ISB) which are designed as networking building-blocks to combat network-outage after large-scale disasters. In the absence of Internet, it leverages (a) the presence of active smartphone users as crisis mappers, (b) inherent mobility of rescue vehicles as data mules, and (c) presence of few pre-deployed ISBs in a disaster-hit locality. CRIMP creates a Wi-Fi ad-hoc network to opportunistically aggregate captured information, processes it, and finally embeds it on maps to generate semi-real-time 'Local Crisis Map' (LCM) in a decentralized way. It considers issues unique to an offline crisis mapping system and implements a channel-sensed, hands-free, scalable, ad-hoc connectivity among devices in proximity for 'role-based' seamless syncing of situational messages, addressing the 'consistency-coverage-quality trade-off'. Extensive lab-scale testing and analysis from some field-level mock drills reveal that CRIMP can speed-up the need assessment and emergency response in time-sensitive situations.